A comparative study of skeletal fluorosis among adults in two study areas of Bangarpet taluk, Kolar - M N Shruthi; Anil Navale Santhuram; H S Arun; B N Kishore Kumar (Wolters Kluwer Medknow Publications, 2016)
Background: Skeletal fluorosis is a crippling disease resulting from excessive exposure to high fluoride from different sources. Objectives: To assess the prevalence of skeletal fluorosis in Bangarpet taluk of Kolar, to compare various epidemiological factors influencing the occurrence of skeletal fluorosis among the two groups with differential water fluoride levels, and to estimate fluoride levels in all the sources of drinking water in study areas. Methods: A cross-sectional study was conducted among the adults of three randomly selected villages of Bangarpet taluk, Thimmasandra, Batavarahalli, with high (>1.5 mg/L) and Maddinayakanahalli with normal (<1.0 mg/L) fluoride levels. A house-to-house survey was conducted by administering a semi-structured questionnaire. Skeletal fluorosis was assessed by three simple physical tests in the field followed by radiological confirmation among the positives. Fluoride levels of drinking water sources were estimated by the ion-electrode method. Chi-square and Fisher's exact tests were used as tests of association. Results: The prevalence of skeletal fluorosis at field level in both high and normal fluoride groups was 5.0%. Water fluoride levels in Thimmasandra, Batavarahalli, and Maddinayakanahalli were 4.13 mg/L, 2.59 mg/L, and 0.61 mg/L, respectively. Among the subjects with skeletal fluorosis, a significant difference was observed between socioeconomic status and prevalence of skeletal fluorosis in both high and normal fluoride groups (P < 0.05). Conclusion: Skeletal fluorosis is a threat among elderly in Bangarpet taluk, Kolar district.